Guido d’Arezzo e il dirozzamento degli «stupidi cantori» - Cesarino Ruini (Musica Docta)
The development and flourishing of European art music was made possible above all by the “invention” of musical notation. This invention, in turn, served a political-cultural purpose: to ensure the standardisation of the liturgical chant of the Latin Church (the so-called Gregorian chant) throughout the territory of the Carolingian Empire. The study and understanding of this process is essential for anyone wishing to find an explanation for the immense power of expansion exerted by the musical art of the West in the centuries that followed. The key stages are well known: the introduction of neumatic notation, which was practised in various forms from the 9th century onwards, followed by the invention of a notation system by Guido of Arezzo (11th century), which made it possible to determine the pitch of notes unambiguously. This last development was a response to a pedagogical and didactic concern: the monk of Pomposa wanted to refine the art of the «stupidi cantori» (stupid singers), relieving them of the arduous task of memorising the Gregorian repertoire, which distracted them from worship and from the study of sacred and secular literature. Any “transmission of knowledge” that does not want to be reduced to a mere evolutionary collection of concepts, but also does not want to misinterpret the unifying aspiration that, two centuries later, underpinned both neume writing and the invention of the musical staff, by denouncing it as an odious “imperialistic” arrogance, will have to read this process in the light of the educational programme that Guido d’Arezzo clearly outlined in his Epistola ad Michaelem.